Experimental and computational study on anti-gastric cancer activity and mechanism of evodiamine derivatives - Liu, Jingli; Xue, Yingying; Bai, Kaidi; Yan, Fei; Long, Xu; Guo, Hui; Yan, Hao; Huang, Guozheng; Zhou, Jing; Tang, Yuping (Frontiers in Pharmacology, 2024)
Introduction: Human topoisomerase 1 (TOP1) is an important target of various anticancer compounds. The design and discovery of inhibitors targeting TOP1 are of great significance for the development of anticancer drugs. Evodiamine and thieno [2, pyridine hybrids show potential antitumor activity. Herein, the anti-gastric cancer activities of these hybrids were investigated.Methods: The inhibitory effects of different concentrations of ten evodiamine derivatives on the gastric cancer cell line SGC-7901 were assessed using a methyl thiazolyl tetrazolium assay. Compounds 1 and 6 strongly inhibited gastric cancer cell proliferation, with inhibition rates of 81.17±5.08% and 80.92±2.75%, respectively. To discover the relationship between the structure and activity of these two derivatives, density functional theory was used to investigate their optimized geometries, natural population charges, frontier molecular orbitals, and molecular electrostatic potentials. To clarify their anti-gastric cancer mechanisms, molecular docking, molecular dynamics simulations, and binding free energy calculations were performed against TOP1.Results: The results demonstrated that these compounds could intercalate into the cleaved DNAbinding site to form a TOP1-DNA-ligand ternary complex, and the ligand remained secure at the cleaved DNA-binding site to form a stable ternary complex. As the binding free energy of compound EVO-1 with TOP1 (-38.33 kcal•mol -1 ) was lower than that of compound EVO-6 (-33.25 kcal• mol -1 ), compound EVO-1 could be a more potent anti-gastric cancer agent than compound EVO-6. Discussion: Thus, compound EVO-1 could be a promising anti-gastric cancer drug candidate. This study may facilitate the design and development of novel TOP1 inhibitors.